Disclosure Decisions by Firms and the Competition for Price Efficiency - FISHMAN, MICHAEL J.; HAGERTY, KATHLEEN M. (Journal of Finance, 1989)
ABSTRACT This paper develops a model of the relationship between investment decisions by firms and the efficiency of the market prices of their securities. It is shown that more efficient security prices can lead to more efficient investment decisions. This provides firms with the incentive to increase price efficiency by voluntarily disclosing information about the firm. Disclosure decisions are studied. It is shown that firms may expend more resources on disclosure than is socially optimal. This is in contrast to the concern implicit in mandatory disclosure rules that firms will expend too few resources on disclosure.